Clinico-pathologic Parameters for Prediction of Microsatellite Instability in Colorectal Cancer - Jung, Sang-Bong (Korean Cancer Association, 2012)
PURPOSE: Although the incidence of microsatellite instability (MSI) accounts for 10-15% of cases of colorectal cancer, its clinical application for all colorectal cancers has widened. We attempted to identify clinical and pathological parameters that may be helpful in selection of patients with MSI-high (MSI-H). MATERIALS AND METHODS: A total of 120 resected colorectal cancers were enrolled retrospectively for this MSI study. Polymerase chain reaction (PCR) and denaturing high performance liquid chromatography and/or real time PCR methods with five markers and immunohistochemistry (IHC) for MLH1 and MSH2 were performed for analysis of cancer and blood specimens. Clinico-pathologic parameters, including IHC, were investigated in order to determine their usefulness as predictive factors of MSI. RESULTS: Among 120 cases of colorectal cancer, MSI was observed in 15 cases (12.5%), including 11 cases of MSI-H and four cases of MSI-low. Patients with MSI were younger, less than 50 years old, had a family history of cancer, Rt. sided colon cancer and/or synchronous multiple colorectal cancer, mucinous histologic type, and serum carcinoembryonic antigen group in the normal range. Results of multivariate analysis showed Bethesda guidelines, Rt. sided and/or synchronous multiple colorectal cancer, and negative expression of IHC for MLH1, which was consistently associated with MSI-H. MSI-H colorectal tumors have met at least one of these three parameters and their sensitivity and specificity were 100% and 72.5%, respectively. CONCLUSION: Bethesda guidelines, tumor location, and negative expression of MLH1 protein are important parameters for selection of patients with colorectal cancers for MSI testing. MSI testing is recommended for patients showing any of these three parameters.